Reformasi Sistem Pendidikan Islam di Indonesia - Siswadi Siswadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Islam education reformation is an absolute demand. Everyone effort, especially teacher, lecturer, politician, stakeholder, state, or private sector surely bring positive impact to education, include Islamic education. However, education system implemented today, in school or ex-scroll, remain contain weakness and deterioration. This paradigm triggers the rise of Islam education reforms spirit. This article show how Indonesian education figure see Islamic education condition in Indonesia. Meanwhile, by and large we would about reforms Islamic education effort that more constructive ad relevant with change and development on this globalisation and industrialisation era.